Hubungan antara Kelekatan Aman dengan Ayah dan Kualitas Relasi Romantis pada Dewasa Awal - Vania Susanto; Diana Permata Sari (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2021)
This research aimed to know the correlation between secure attachment with father and the quality of romantic relationships in emerging adulthood women. The hypothesis stated that there was a significant positive correlation between secure attachment with father and the quality of romantic relationships in emerging adulthood women. This research was a quantitative research with convenience sampling. The method of data collection in this research used two adaptation scales, namely the IPPA (Inventory of Parent and Peer Attachment) for father-daughter attachment and the PBSC (Partner Behaviours as Social Context Scale) for the quality of romantic relationships. The respondents of this research were 543 emerging adulthood women who were 18-25 years old and in dating relationships. The try out of scales get reliability of coefficients on secure attachment scale was 0.95 and the quality of romantic relationships was 0.881. The research data was analyzed using Spearman’s rho one-tailed correlation technique because the data was not normally distributed. The result showed that attachment is correlated positively with the quality of romantic relationships with the value of the correlation test was 0.165 and significance level (p) was 0.00 (p0.01). Based on this, it can be concluded that there was a significant positive relationship between secure attachment and the quality of romantic relationships.